The Origin of the Residual Carbon in LiFePO4 Synthesized by Wet Milling - Park, Sung Bin; Park, Chang Kyoo; Hwang, Jin Tae; Cho, Won Il; Jang, Ho (WILEY-V C H VERLAG GMBH, 2011)
This study reports the origin of the electrochemical improvement of LiFePO4 when synthesized by wet milling using acetone without conventional carbon coating. The wet milled LiFePO4 delivers 149 mAhg(-1) at 0.1 C, which is comparable to carbon coated LiFePO4 and approximately 74% higher than that of dry milled LiFePO4, suggesting that the wet milling process can increase the capacity in addition to conventional carbon coating methods. UV spectroscopy, elemental microanalysis, and evolved gas analysis are used to find the root cause of the capacity improvement during the mechanochemical reaction in acetone. The analytical results show that the improvement is attributed to the conductive residual carbon on the surface of the wet milled LiFePO4 particles, which is produced by the reaction of FeC2O4 center dot 2H(2)O with acetone during wet milling through oxygen deficiency in the precursor.
Keywords: ELECTROCHEMICAL PROPERTIES; COATED LIFEPO4; PHOSPHO-OLIVINES; RATE PERFORMANCE; COMPOSITE